Single incision laparoscopic cholecystectomy: A review on the complications - Sofie Fransen; L Stassen; N Bouvy (Journal of Minimal Access Surgery, 2012)
Background: The aim of this study was to establish the incidence of postoperative complications after single incision laparoscopic cholecystectomy. Materials and Methods: A literature search was performed using the PubMed database. Search terms included single incision laparoscopic cholecystectomy, single port cholecystectomy, minimal invasive laparoscopic cholecystectomy, nearly scarless cholecystectomy and complications. Results: A total of 38 articles meeting the selection criteria were reviewed. A total of 1180 patients were selected to undergo single incision laparoscopic cholecystectomy. Introduction of extra ports was necessary in 4% of the patients. Conversion to open cholecystectomy was required in 0.4% of the patients. Laparoscopic cholangiography was attempted in 4% of the patients. The incidence of major complications requiring surgical intervention or ERCP with stenting was 1.7%. The mortality rate was zero. Conclusion: Although the number of complications after single incision laparoscopic cholecystectomy seems favourable, it is too early to conclude that single incision laparoscopic cholecystectomy is a safe procedure. Large randomised controlled trials will be necessary to further establish its safety.